Mekanisme Persiapan Pemekaran Desa Tunan Taka Di Kelurahan Petung Kecamatan Penajam Kabupaten Penajam Paser Utara - Rukaiyah, St; Herlinah, Herlinah; Hamid, Mulyadi (Movere Journal, 2025)
This study aims to identify and analyze various aspects related to the preparation for the expansion of Tunan Taka Village in Petung Village, Penajam District, Penajam Paser Utara Regency. This study employs a descriptive qualitative approach to understand the preparation strategy for the expansion of Tunan Taka Village in Petung Village, Penajam District, Penajam Paser Utara Regency. Data is collected through interviews, observations, and document analysis to assess strategic steps, obstacles faced, feasibility assessment, expected impacts, and the role of relevant agencies and government policies in supporting village expansion. The research results indicate that the preparation for the expansion of Tunan Taka Village involves strategic steps such as proposal submission, feasibility surveys, coordination with relevant agencies, and community involvement. Major obstacles in the expansion process include administrative issues, infrastructure, and inter-party coordination. Tunan Taka Village is considered feasible for expansion based on existing economic, social, and infrastructure potential. The expansion of Tunan Taka Village is expected to improve community welfare and accelerate regional development by increasing government attention to public services and economic development. The role of relevant agencies and government policies is crucial in supporting the expansion process, where coordination and policy support can ensure that the expansion process complies with regulations and is effective.